Google Sites Innovation as A Web-Based Learning Media on Substance Material and Its Changes - Arrahma., A.; Linda., R.; Azizahwati, A. (Journal of Science Education Research, 2025)
The use of Google Sites in learning contexts is still limited because many teachers have not fully utilized the potential of this media. They don't realize that Google Sites has the advantage of creating interesting and interactive learning experiences. Therefore, innovative efforts are needed to optimize the use of Google Sites as an effective learning medium. The aim of this research is to innovate learning media based on Google Sites on substance material and its changes in a valid and practical way. The method used is a 4D model with define, design, develop and disseminate steps. The research sample consisted of 20 class VII students at SMPN 6 Tapung. Data collection techniques for field studies which include observation, interviews and distribution of student response questionnaires. The data analysis technique in this research uses descriptive analysis techniques which explain the results of product development in the form of Google Sites learning media, with data from validation results and practicalities that describe the results of the research conducted. Based on the analysis, it was found that Google Sites-based learning media was very valid with an average validity of 3.68 and practical to use with an average of 3.11. The author makes the following suggestions: science subject teachers need to create varied learning and increase knowledge in technological media to improve efficient and advanced learning.